Christianisme et monde ouvrier - Baubérot, Jean (1941-....); Bédarida, François (1926-2001); Maitron, Jean (1910-1987)
ill. Éd. remaniée des textes précédemment parus dans "Le Mouvement social", 57, 1966 Bibliogr., 1 p.